Analisis Pengendalian Internal pada Sistem Akuntansi Pengeluaran Kas - Sandora, Yulia; Fransisca, Septiani (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
Every company strives to optimize its profit. Achieving this goal requires a reliable and structured accounting system. The cash receipts accounting system plays a crucial role in a company's operations. This study focused on Permata Hospital, Palembang. The objective of this study was to analyze internal control in the cash disbursement accounting system, which involves three related departments: the cashier, the treasurer, and the financial coordinator. This study employed qualitative analysis techniques, incorporating interviews, documentation, and observation in the data collection process. This study detailed a flowchart of each department within the cash receipts accounting system and provided a systematic explanation of the procedures. It also ensured data reliability by reducing, analyzing, and drawing conclusions. This study presented a discussion of the functions, documents, records, and verification checklist of internal control elements. The results showed a satisfactory level of achievement, with 83.3% of the internal control elements at Permata Hospital, Palembang, being met.